Study of Babak River water quality using physical and chemical parameters in Kebon Kongok landfill (Lombok, Indonesia) - Meiliyadi, Lalu Ahmad Didik; Rahman, Muhammad Zainur; Zain, Zahida Aliatu (Institute of Advanced Engineering and Science, 2024)
The study has been conducted on the water quality level of the Babak River around Kebon Kongok landfill, Lombok. This research was conducted considering that water has many benefits in the daily lives of people. This research uses an experimental method by analyzing physical parameters (temperature, conductivity, pH, and total dissolved solids (TDS)), and chemical parameters in the form of heavy metal content lead (Pb), iron (Fe), manganese (Mn), and copper (Cu)). Analysis results were compared with quality standards based on Ministry of Health Regulation No. 32 of 2017 concerning water quality. Based on the study, it was found that the farther the distance of water measured from the source of pollution, the value of the physical and chemical parameters of water will be smaller. Most of the physical parameter test results show the Babak River water quality is still at the safe threshold limit but there is 1 point of river water that is polluted due to the distance that is too close to the active zone. Chemical parameters show the results of heavy metal content below the threshold limit. Analysis of the water quality shows that the water is still in good condition, which is below the threshold set by the Indonesian government.